Ally the dolphin fairy - Meadows, Daisy (New York : Scholastic, 2011)
Rachel and Kirsty help Ally the Dolphin Fairy track down Ally's dolphin friend Echo, who is guarding one of the pieces to the enchanted conch shell near the Sealife Center.
3.7
K-3
K-3.
760
Keywords: Fairies -- Juvenile fiction; Dolphins -- Juvenile fiction; Goblins -- Juvenile fiction; Fairies -- Fiction; Dolphins -- Fiction; Goblins -- Fiction; Fantasy; Fairies -- Fiction; Dolphins -- Fiction; Goblins -- Fiction; Fantasy fiction; Fantasy fiction